English Communication Skills (ECS) of Grade 9 Learners: The Basis for Designing an ECS Intervention Program - Angelyn Garcitos; Ma. Corazon Gargar; Zaillah Lomocso; Ronjell Amacna; Ruel T. Bonganciso (Journal of English as A Foreign Language Teaching and Research, 2024)
English Communication Skills (ECS) are crucial in the globalized context, yet the Philippines' ranking of 77th out of 81 countries highlights a significant proficiency gap. Consequently, there is an urgent need for targeted intervention programs to address these challenges among Filipino students.  This research aimed to evaluate the English Communication Skills (ECS) of Grade 9 students at High School in Philippines, focusing on speaking and writing proficiency levels and the relationship between them, to develop an intervention program. Utilizing a descriptive research design with a quantitative approach, the study involved 40 Grade 9 students selected through random sampling. Data were collected using a researcher-made survey questionnaire, complemented by tests employing the WIDA Speaking and Writing Interpretive Rubrics for a detailed analysis of speaking and writing capabilities. The analysis was conducted using statistical methods to yield descriptive statistics and the Pearson R correlation for assessing the relationship between speaking and writing skills. The results indicated that while students perceived their ECS as satisfactory, the actual assessments did not meet the expected standards, and a very low correlation was found between speaking and writing proficiency. This gap emphasizes the necessity for targeted intervention programs tailored to the specific needs of students to enhance their ECS. The study concludes with the recommendation for developing pedagogical strategies that focus on the identified areas of improvement in ECS among Grade 9 learners.